The role of cosmetic surgery in the embodied experience of female beauty: a narrative study in Bloemfontein, South Africa - Heggenstaller, Alessandra Kim (University of the Free State, 2017)
Nowadays, the concept of human ‘beauty’ is intricately linked to that of identity: beauty is seen as bringing success in occupation, love, and marriage. Accordingly, beauty is often treated like a commodity—social status is attributed to it, and negotiated with it. The way in which female beauty is constructed and manipulated by popular culture and via the mass media, leads many women to reshape their physical appearance in order to conform to what is widely regarded as beautiful, ideal, and in line with current trends. And this appears to occur irrespective of women’s economic position or cultural heritage. The media holds particular sway in constructing beauty ideals by encouraging the everyday woman to constantly evaluate her physical appearance. And out of the resulting sense of needing self-improvement many women refer to, and then conform to, a (mostly Westernised) notion of generic sameness. Cosmetic surgery is a growing phenomenon influencing women’s lives all around the world and is growing in popularity in South Africa, where this research is located. The study aims to understand how beauty is perceived, and what impact a rejected or unwanted physical feature may have on an individual’s sense of self and on her life-world. I argue that when a woman experiences cosmetic surgery as empowering in terms of her appearance and her identity, this changes how she perceives and experiences herself; and that this re-negotiation of self-concept will influence how she engages her life-world and social reality. This study is firmly situated in sociological theory. It applies theoretical insights from Alfred Schütz’s phenomenological approach, Peter Berger and Thomas Luckmann’s social construction of reality, and John Creswell’s interpretivist methodology. Because it is vital to understand the gender dynamics at play when women undertake cosmetic surgery, particular attention is paid to feminist thought via the works of Kathy Davis and Iris Marion Young. The research is positioned in a qualitative research design. After obtaining ethical clearance for the study, I negotiated access to a cosmetic surgery practice, and with the help and support of the registered cosmetic surgeon, participants were recruited. The ten participants are from a white middle-to-upper socio-economic class in Bloemfontein, South Africa. Criteria for participation included women undergoing only the cosmetic procedures of blepharoplasty, liposuction, abdominoplasty, breast augmentation and breast lift. Data was collected in semi-structured, one-on-one, in-depth interviews, guided by interview schedules. Interview processes allowed participants to expand on their lived experiences, subjective thoughts, inter-subjective encounters, and their feelings and emotions. Interviews were audio recorded and transcribed verbatim. The narratives were thematically analysed and mined to unearth the hidden depth and richness of the cosmetic experience. Key themes that unfolded and which are discussed in the analysis chapters are ‘beauty and its (re)negotiation’, ‘identity and femininity’, ‘cosmetic surgery and (dis)empowerment’, ‘finding the courage’, ‘the risks’, and ‘cosmetic surgery changing lives’. This study expands on existing knowledge and common perceptions of ‘beauty’ by revealing the subjective-voice of ten women and their cosmetic experience. Insights are gained on self-empowerment and embodiment and how these interface with each participant’s perceptions of herself, her femininity, and her sense of self-worth. Emphasis is also given to how the thoughts, feelings, and emotions before and after their cosmetic interventions impact on participants’ everyday life-world and (re)construction of their proximate social reality. The focus on South Africa is unique as most studies on cosmetic surgery are from the USA and Europe. Research findings also contribute to understanding cosmetic surgery in this day and age, by showing that simplistic and stereotypical judgements of the phenomenon and the many ordinary women who opt for it are limited and limiting.
Thesis (D.Phil. (Sociology))--University of the Free State, 2017
Keywords: Cosmetic surgery; Beauty; Femininity; Identity; Gendered embodiment; (Dis)empowerment; Life-world; Phenomenology; Social constructivist; Interpretivist; Feminist thinking